1994
DOI: 10.1111/j.1439-0450.1994.tb00204.x
|View full text |Cite
|
Sign up to set email alerts
|

Trenbolone Acetate Induced Changes in the Genital Tract of Male Pigs

Abstract: Eleven entire and twelve castrated male pigs were implanted with trenbolone acetate and the effects of the treatment on genital tract macro-and microscopical modifications were evaluated and compared to non-implanted animals. In entire male pigs a reduction of testicular weight and size was observed as a consequence of the treatment (< 0.001), but no important modifications were found in bulbourethral gland and seminal vesicles macroscopically. Castrated non-implanted males had bulbourethral gland atrophy (P <… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Legoshin et al (1994) observed that there was a correlation between using zeranol and the behaviour of bulls, which 'spent more time idling, eating and ruminating than controls. ' Lopez-Bote et al (1994) demonstrated that trenbolone changed the genital tract in male pigs. Liehr (1995) inferred that hormones cause damage to prostatic tissue and are mutagenic to DNA.…”
Section: The Emergence Of the Sps Agreementmentioning
confidence: 98%
“…Legoshin et al (1994) observed that there was a correlation between using zeranol and the behaviour of bulls, which 'spent more time idling, eating and ruminating than controls. ' Lopez-Bote et al (1994) demonstrated that trenbolone changed the genital tract in male pigs. Liehr (1995) inferred that hormones cause damage to prostatic tissue and are mutagenic to DNA.…”
Section: The Emergence Of the Sps Agreementmentioning
confidence: 98%
“…81 Lopez-Bote et al, (1994) demonstrated that trenbolone changed the genital tract in male pigs. 82 Liehr (1995) inferred that hormones cause damage to prostatic tissue and mutagenic DNA. 83 However, all of these studies differed from the issue at hand as they were injected/fed directly to the animals as opposed to passing first through another animal.…”
Section: [Emphasis Added]mentioning
confidence: 99%